Wealth effects associated with announcements of hybrid securities in an emerging country: evidence from Malaysia - Abdul Rahim, Norhuda; Abdul Rahman, Fauziah (Universiti Putra Malaysia Press, 2015)
This paper examines the market reaction to hybrid security announcements in an emerging country, specifically Malaysia, from January 1996 to December 2009. The results indicated that announcements of the intention to issue convertible bonds in Malaysia are significantly associated with negative abnormal returns of 1.10% (significant at the 10% level) on the event window of (-1, 1). On the other hand, announcements of the intention to issue warrant-bonds document significantly positive abnormal returns of 2.25% (significant at the 5% level) on the same event window. The ‘univariate’ test confirmed that the wealth effect associated with the announcement of the intention to issue warrant-bonds is larger (i.e., more positive) than convertible bonds, in line with a few studies conducted in different markets. The findings of this study highlight that listed firms with high risk uncertainty in Malaysia contribute to more negative abnormal returns in comparison to lower risk uncertainty firms.